2023
DOI: 10.1002/ps.7703
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of novel salicylaldehyde derivatives incorporating an α‐methylene‐γ‐butyrolactone moiety as fungicidal agents

Abstract: BackgroundPlant diseases caused by phytopathogenic fungi and oomycetes pose a serious threat to ensuring crop yield and quality. Finding novel antifungal candidates based on natural products is one of the critical methods for developing effective and environmentally friendly pesticides. In this study, a series of salicylaldehyde derivatives containing an α‐methylene‐γ‐butyrolactone moiety were designed, synthesized, and their fungicidal activities were evaluated.ResultsThe bioassay studies indicated that compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The inoculation methods for R. solani have been previously documented. 35,36 In Vivo Antifungal Activities against B. cinerea. Based on the in vitro antifungal activity test, compound C24 against B. cinerea were further evaluated in vivo on tomato.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The inoculation methods for R. solani have been previously documented. 35,36 In Vivo Antifungal Activities against B. cinerea. Based on the in vitro antifungal activity test, compound C24 against B. cinerea were further evaluated in vivo on tomato.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Effect of the enzyme activity of complex III on R. solani Based on earlier studies, we found that one of the targets of carabrone is mitochondrial complex III. [30][31][32] Thus, MBL derivatives containing benzothiophene fragments may also target mitochondrial complex III because they share the same pharmacophore. The mycelia of R. solani were treated with compound 2 and famoxadone at concentrations of 25 and 50 mg L −1 , respectively, and the untreated mycelia served as a blank control.…”
Section: Relative Conductivity %mentioning
confidence: 99%
“…Plant pathogens seriously affect food security and yield, and the use of fungicides is the most direct and effective way to control crop diseases. , According to FRAC, more than 230 small-molecule fungicides are currently commercialized, providing a guarantee for a global food supply and social security and stability. However, with the long-term use of traditional chemical fungicides, pathogen resistance is becoming more and more serious, and the ecological environment is also under threat. Therefore, the development of new, green, safe, and efficient fungicides is indispensable and also in line with the concept of green sustainable development.…”
Section: Introductionmentioning
confidence: 99%